IDEF* modeling of a post-assembly IC (Integrated Circuit) manufacturing process - Sim, Alvin Chin Beng. (2008)
Develop a detailed description of a post assembly IC manufacturing process from the five different views using the IDEF* methodology namely function, information, process, resource and organisation.